Effect of the addition of laying hens manure to the straw on gasification efficiency in updraft gasifier under air atmosphere. (25th May 2023) - Junga, Robert; Tańczuk, Mariusz; Sobek, Szymon; Chabiński, Michał; Ziółkowski, Łukasz; Werle, Sebastian
Abstract: There is a gap for research dedicated to co-gasification of laying hens manure (LHM) with commonly used litter such as wheat straw. The lack of comprehensive studies for such blends with broad range of air–fuel equivalent ratios (AFER) is also a challenge. The study was performed on a laboratory scale fixed bed updraft reactor supplied with straw and LHM blends of different mixing ratios (25, 50, 75%) and at low (0.12–0.28) and high (0.30–0.45) AFER ranges. The main objective of the research was to recognize the impact of the LHM addition on the quality of the producer gas and process efficiency. For higher ranges of the AFER, the LHV of the producer gas remains in a range of 3.3–3.4 MJ/m 3 depending of the fuel blend ratio, yielding the cold gas efficiency about 60% and the carbon conversion efficiency in range of 82–94%. Highlights: Updraft gasification of straw with laying hens manure was experimentally verified. Manure addition was tested for gasification efficiency under different air ratios. The more manure in the blend, the worse quality of the gas, regardless of air ratio. Calorific value of producer gas increases by 6.4% for air ratios higher than 0.3. CCE and CGE more dependent on manure addition for air ratios below 0.3.